Complexes of β-lactoglobulin and high methyl-esterified pectin as a one-shot delivery system for reinforcing oil/water interfaces. Issue 37 (8th September 2021) - Ramamirtham, Sashikumar; Williams, Martin A.K.; Zare, Davoud; Weeks, Mike; Whitby, Catherine P.
Abstract : Once protein–polysaccharide complexes reach the interface, proteins adsorb while remaining electrostatically bonded to the polysaccharide. The polysaccharide reinforces the interfacial film by linking the adsorbed protein molecules together. Abstract : Electrostatic complexation of negatively charged polysaccharides with β-lactoglobulin (β-lg) has been shown to bolster the protein films at oil/water interfaces thereby improving emulsion stability. However, recent sub-phase exchange experiments demonstrated that highly charged polysaccharides such as low methyl-esterified pectin are complementary only if sequentially introduced to a pre-formed interfacial β-lg film. In this study, results of transient interfacial shear rheology show that, by using high-methylesterified pectins instead, complexes can be formed in pre-mixed solutions with β-lg at pH 4 that can lead to reinforced protein films at dodecane/water interfaces. Using this one-shot adsorption of such complexes, pectins as well as short chain polysaccharides like homogalacturonan nearly doubled the steady state shear elastic moduli as compared to that of a pure β-lg film. The lag times of film formation were established to be primarily decided by the charge density and pattern on the polysaccharide. Based on the results from mixed solutions of β-lg monomers, it is proposed that the polysaccharide at pH 4 strengthens the resulting interfacial layer by concatenating adsorbed β-lg molecules thereby establishing cross-links in the aqueous phase.